Possible applications of LCA in environmental engineering technologies - Bajdur, Wioletta; Włodarczyk-Makuła, Maria (Instal, 2023)
Environmental Life Cycle Assessment – LCA described in the ISO 14000 series standards is one of the most important and reliable techniques for assessing the environmental impact of technologies and products. Currently, it has an established position as a research tool in areas of science and practice related to the environment. The impact of new or existing technologies and products on the environment is one of the key problems in the Member States of the European Union, where we strive to maximize material recovery and reuse of waste. It is technologically and economically justified to recycle waste or use it as secondary raw materials, as well as neutralize its waste at the point of generation. One of the innovative solutions is the chemical modification of polymer waste to obtain flocculants used in industrial wastewater treatment processes. Currently, an assessment of the impact of technological processes and by-products on the environment in their life cycle is being carried out. LCA analysis confirms the effective use of new polymers and, in the long run, their environmentally safe production. The examples presented make it possible to follow the procedure for assessing the impact of the life cycle of production technologies and products on the environment.
Keywords: LCA; technologies; by-products; environment; engineering materials